Automatic fiscal stabilizers in Sweden 1998 - 2009 - Martin Flodén (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
In this note, I examine how the responsiveness of the Swedish public budget to business-cycle conditions has developed between 1998 and 2009. I document substantial changes in three components behind the budget elasticity: (i) the average level of personal income taxes has fallen substantially, (ii) the progressivity of personal income taxation has increased, and (iii) spending on unemployment compensation has fallen. The first two changes have opposing effects on the budget elasticity, and I find that the higher progressivity has had a marginally larger impact on the elasticity than the tax cuts. Also allowing for the lower unemployment compensations, the three effects add up to a small and non-substantial fall in the budget elasticity. Considering that most of the components behind the budget elasticity are imprecisely estimated, there is no clear evidence that the Swedish budget elasticity has changed during the last decade.
Keywords: E62; H30; H60; 330; Automatic stabilizers; budget elasticity; fiscal policy; stabilization policy; Finanzpolitik; Konjunkturpolitik; Eingebauter Stabilisator; Öffentlicher Haushalt; Schweden